Stapled NRPS enhances the production of valinomycin in Escherichia coli - Huang, Shuhui; Ba, Fang; Liu, Wan‐Qiu; Li, Jian (Biotechnology and bioengineering, 2023)
Nonribosomal peptides (NRPs) are a large family of secondary metabolites with notable bioactivities, which distribute widely in natural resources across microbes and plants. To obtain these molecules, heterologous production of NRPs in robust surrogate hosts like Escherichia coli represent a feasible approach. However, reconstitution of the full biosynthetic pathway in a host often leads to low productivity, which is at least in part due to the low efficiency of enzyme interaction in vivo except for the well‐known reasons of metabolic burden (e.g., expression of large NRP synthetases—NRPSs with molecular weights of >100 kDa) and cellular toxicity on host cells. To enhance the catalytic efficiency of large NRPSs in vivo, here we propose to staple NRPS enzymes by using short peptide/protein pairs (e.g., SpyTag/SpyCatcher) for enhanced NRP production. We achieve this goal by introducing a stapled NRPS system for the biosynthesis of the antibiotic NRP valinomycin in E. coli. The results indicate that stapled valinomycin synthetase (Vlm1 and Vlm2) enables higher product accumulation than those two free enzymes (e.g., the maximum improvement is nearly fourfold). After further optimization by strain and bioprocess engineering, the final valinomycin titer maximally reaches about 2800 µg/L, which is 73 times higher than the initial titer of 38 µg/L. We expect that stapling NRPS enzymes will be a promising catalytic strategy for high‐level biosynthesis of NRP natural products. Nonribosomal peptides (NRP) are important natural products synthesized by large NRP synthetases (NRPS). To enhance their catalytic efficiency, the authors report a new strategy to staple NRPS by using short peptide/protein pairs (e.g., SpyTag/SpyCatcher). The results demonstrate that stapled NRPS enables high‐level biosynthesis of the NRP antibiotic valinomycin in a heterologous host such as Escherichia coli.